VD_FINDINFO HC / 2023 / 852 vom 12. Oktober 2023 - VD Tribunal cantonal (2023)
ÉTAT DÉFECTUEUX DU VÉHICULE, GARANTIE EN RAISON DES DÉFAUTS DE LA CHOSE, DISSIMULATION{CHOSES, FAITS}, ACTION RÉDHIBITOIRE, VENTE | 199 CO, 200 CO, 60 CPC (CH)